(untitled) (Teaching and Learning Inquiry, 2019)
There are many general books and articles on publishing in peer-reviewed journals, but few specifically address issues around writing for journals focused on the Scholarship of Teaching and Learning (SoTL). One of the challenges of beginning to write about teaching and learning is that most scholars have become interested in exploring these issues in higher education alongside their disciplinary interests and have to grapple with a new literature and sometimes unfamiliar methods and genres, as well. Hence, for many, as they write about their projects, they are simultaneously forging their identities as scholars of teaching and learning. We discuss the process of producing four types of SoTL-focused writing for peer-reviewed journals: empirical research articles, conceptual articles, reflective essays, and opinion pieces. Our goal is to support both new and experienced scholars of teaching and teaching— faculty/academics, professional staff, and students—as they nurture and further develop their voices and their identities as scholars of teaching and learning and strive to contribute to the enhancement of learning and teaching in higher education. We pose three related sets of overarching questions for consideration when writing about teaching and learning for peer-reviewed journals and offer heuristic frameworks for publishing in the four specific writing genres listed above. We also discuss how to get started with writing, preparing to submit, and responding to reviewers, focusing on the importance of contributing to and creating scholarly conversations about teaching and learning. Finally, using the metaphor of being in conversation, we argue that writing is a values-based process that contributes to the identity formation of scholars of teaching and learning and their sense of belonging within the SoTL discourse community.